Analisis Kepuasan Pengguna Aplikasi Netflix Mobile di Kota Palembang Menggunakan Metode End User Computing Satisfaction (EUCS) - M, Nys Marliza Tiara; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka; Meiriza, Allsela (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Netflix is a movie streaming media platform that has been used by millions of internet users around the world, including in Indonesia. However, based on user reviews on the Play Store, there are still many users who give poor ratings to the Netflix Mobile application, causing a decrease in rating from 4.3 to 3.8. The purpose of this study is to determine how satisfied users are with the Netflix Mobile application using the End User Computing Satisfaction (EUCS) method with five variables, namely Content, Accuracy, Format, Ease of Use and Timeliness, then the results of the study can later be used as a priority for improvement so that the rating goes up and can be an evaluation material for improving the Netflix Mobile application in the future. Likert scale measurements and questionnaires were used to obtain data for this study, the analysis results of this study show that the variable that has the lowest satisfaction with a value of 74.85% is the Accuracy variable. Therefore, the Netflix Mobile application needs to develop the accuracy of its application performance system in order to minimize errors and always present correct and accurate film information.